Polypharmacy in Primary Care (Research, Society and Development, 2024)
The term polypharmacy can be defined both in relation to the high number of medications used and the length of treatment carried out. The present study aims to analyze the characteristics and consequences of the practice of polypharmacy in primary care. The research is an integrative review of the literature, carried out by searching for articles related to the topic presented in the following scientific databases BVS, SciELO and Google Scholar. After the articles were evaluated using the research inclusion and exclusion criteria, it was possible to select 21 articles to compose the literature review. The articles analyzed show that the practice of polypharmacy is quite common in primary care health services, especially in the elderly population, which is greatly affected by different health problems. Another relevant aspect is the role of health professionals - especially doctors and pharmacists - in this process of increasing the use of medicines, in which there are often both unnecessary prescriptions and a lack of further evaluation of the medication acquired by the patient. Furthermore, the inclusion of the patient in the process of self-assessment of their health status can reduce such cases of polypharmacy. As a consequence of the high consumption of drugs, which are sometimes inappropriate, there are complications in health status and even cases of mortality, as well as public expenses. Therefore, greater multidisciplinary integration in healthcare and a better assessment of patients' health status are effective approaches to managing polypharmacy.